CHALLENGES IN THE USE OF THE E-GOVERNMENT PORTAL AND ELECTRONIC SERVICES IN SERBIA - Gavrilović, Ilija (Political Review, 2025)
Over the past 15 years, Serbia has made significant progress in the field of digitalization and the development of electronic services. A national e-services portal – the eGovernment Portal (Портал еУправа) – has been established, along with numerous other electronic portals (such as the e-Taxes Portal, e-Invoices, Local Tax Administration, etc.), and various e-services (for example, electronic payment of fees and charges under the jurisdiction of the Ministry of the Interior).During the same period, there has been a significant increase in the number of eCitizens – citizens who use the eGovernment Portal – and now more than one-third of Serbia’s population can be considered eCitizens. This progress has also been recognized by relevant international organizations, such as the United Nations, which in 2022 ranked Serbia among the countries with a very high level of eGovernment development and a very high level of eParticipation on its e-Government Development Index (EGDI).However, Serbia still faces key challenges that prevent a larger number of citizens from becoming eCitizens. This, in turn, limits broader electronic civic participation and the possibility of greater involvement in public and political life through new technologies and digital services.Two main challenges stand out: low levels of digital literacy among Serbian citizens, especially when compared to EU member states – and particularly Denmark, which is a global leader in this field, and lack of user support in navigating and using e-services, along with an overall lack of promotion and awareness regarding the benefits of this mode of service delivery. As a result, many people still perceive it as easier to complete tasks in person rather than through digital platforms. This perception threatens Serbia’s ability to keep pace with modern trends in Europe and other developed countries moving toward fully digital public services, and may affect its competitiveness in this domain.To overcome these barriers, it is essential that citizens are not passive observers of changes in the ICT world. Instead, efforts must be made to educate and improve their digital skills. This would be the first part of the solution. The second part lies in the hands of the state, which is expected to play a proactive role by promoting digital literacy, increasing public awareness of e-services, and providing better user support mechanisms.
Keywords: e-government; digitalization; public administration reform; e-Participation; e-Democracy